2016
DOI: 10.1016/j.jrras.2015.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of process parameters for xylanase production by Bacillus sp. in submerged fermentation

Abstract: In this study an attempt was made to optimize the cultural and nutritional conditions for xylanase production by Bacillus species in submerge fermentation process. Whole fermentation process was carried out in 250 ml Erlenmeyer flask with agitation speed of 140 rpm. Bacillus subtilis exhibit maximum xylanase production at initial medium pH of 8, substrate concentration of 2% with inoculum size of 2% at 35 C for 48 h of fermentation period. Further supplementation of sucrose, (NH 4) 2 SO 4 and peptone as a carb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
50
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(69 citation statements)
references
References 24 publications
5
50
1
1
Order By: Relevance
“…Bacillus spp., greatly depend on the amount of available oxygen (Nadeem, Qazi, & Baig, 2009 | 3697 2011; Irfan, Asghar, Nadeem, Nelofer, & Syed, 2016). This seems to support the lower crude fibre content in the FerRB.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Bacillus spp., greatly depend on the amount of available oxygen (Nadeem, Qazi, & Baig, 2009 | 3697 2011; Irfan, Asghar, Nadeem, Nelofer, & Syed, 2016). This seems to support the lower crude fibre content in the FerRB.…”
Section: Discussionmentioning
confidence: 91%
“…Production of starch degrading enzymes such as α ‐amylase and xylanase was enhanced in Bacillus spp. under anaerobic conditions (Divakaran, Chandran, & Pratap, ; Irfan, Asghar, Nadeem, Nelofer, & Syed, ). This seems to support the lower crude fibre content in the FerRB.…”
Section: Discussionmentioning
confidence: 99%
“…Any other carbon sources like fructose, glucose, CMC (carboxymethyl cellulose) and arabinose were produce the less enzyme production. 24 Azeri et al reported that different strains of Bacillus sp. and all exhibit maximum xylanase production by using birch wood xylan as a carbon source.…”
Section: Discussionmentioning
confidence: 99%
“…For the production of cellulase by Bacillus subtilis and Bacillus circulans, pH in the range of 7.0-7.5 was found to be optimum by Ray et al [59]. According to the report of Irfan et al [43], pH 8 was the best among the pH values of the medium for xylanase production by B. subtilis BS04 and B. megaterium BM07 in submerged fermentation. In addition, lower pH, i.e., 4 and higher pH, i.e., 10 of the medium retards xylanase secretion drastically.…”
Section: Resultsmentioning
confidence: 98%
“…The optimum temperature for enzyme production by an organism may vary since it is likely to affect growth of the organism. Irfan et al [43] reported that the three bacterial strains used in the study did not grow well at 25ºC and thus resulted in decreased enzyme production. B. subtilis BS04 showed highest enzyme production at 35ºC.…”
Section: Resultsmentioning
confidence: 99%